The complete mitochondrial genome of Cyprinus Carpio Var. Guilin rice flower carp and its phylogeny in Cyprinidae - Dong-Mei Ma; Jia-Jia Fan; Hua-Ping Zhu; Zhang-Han Huang (Mitochondrial DNA. Part B. Resources, 2019)
The complete mitochondrial genomic DNA of Cyprinus carpio var. Guilin was 16,582 bp in length, including 22 transfer RNA genes, 13 protein-coding genes, 2 ribosomal RNA genes, and a D-loop region. Phylogenetic analysis indicated that it was most closely related to Cyprinus carpio isolate Oujiang. The results will provide a reference for further studies on the genetic relationships and evolution process of Cyprinus carpio variants in Cyprinidae.